Metabolic syndrome in bipolar disorder and schizophrenia: dietary and lifestyle factors compared to the general population. (13th December 2013) - Bly, Michael J; Taylor, Stephan F; Dalack, Gregory; Pop‐Busui, Rodica; Burghardt, Kyle J; Evans, Simon J; McInnis, Melvin I; Grove, Tyler B; Brook, Robert D; Zöllner, Sebastian K; Ellingrod, Vicki L
<x xml:space="preserve">Abstract</x> Objective Since a poor diet is often cited as a contributor to metabolic syndrome for subjects diagnosed with bipolar disorder and schizophrenia, we sought to examine dietary intake, cigarette smoking, and physical activity in these populations and compare them with those for the general population. Methods Individuals diagnosed with bipolar disorder (n = 116) and schizophrenia (n = 143) were assessed for dietary intake, lifestyle habits, and metabolic syndrome and compared to age‐, gender‐, and race‐matched subjects from the National Health and Nutrition Examination Survey (NHANES) 1999–2000. Additionally, matched subgroups within the patient populations were compared to elicit any differences. Results As expected, the metabolic syndrome rate was higher in the samples with bipolar disorder (33%) and schizophrenia (47%) compared to matched NHANES controls (17% and 11%, respectively), and not different between the patient groups. Surprisingly, both subjects with bipolar disorder and those with schizophrenia consumed fewer total calories, carbohydrates and fats, as well as more fiber (p < 0.03), compared to NHANES controls. No dietary or activity differences between patient participants with and without metabolic syndrome were found. Subjects with schizophrenia had significantly lower total and low‐density cholesterol levels (p < 0.0001) compared to NHANES controls. Subjects with bipolar disorder smoked less (p = 0.001), exercised more (p = 0.004), and had lower body mass indexes (p = 0.009) compared to subjects with schizophrenia. Conclusions Counter to predictions, few dietary differences could be discerned between schizophrenia, bipolar disorder, and NHANES control groups. The subjects with bipolar disorder exhibited healthier behaviors than the patients with schizophrenia. Additional research regarding metabolic syndrome mechanisms, focusing on non‐dietary contributions, is needed.